Горячий снег: роман / Юрий Бондарев - Бондарев Юрий Васильевич (Азбука-классика, 2017)
Экземпляры: аб. ЦБ (20190218) / Инвентарный номер: 6186 / Цена: / Авт.знак: Б 81 / ГРНТИ: 17.82.30 / ББК: 84 (2Рос=Рус)6-44